Typification and taxonomic remarks of Indobanalia (Amaranthaceae) in India - Iamonico, Duilio; Arya, Sindhu; Kumar, Venugopalan Nair Saradamma Anil (Phytotaxa, 2021)
Indobanalia thyrsiflora is an endemic species occurring in peninsular India (Andhra Pradesh, Karnataka, Kerala and Tamil Nadu States) and Sri Lanka. A nomenclatural study of the basionym Banalia thyrsiflora, published by Moquin-Tandon in Candolle’s Prodromus (year 1849), is carried out and the name is lectotypified on a specimen deposited at P (barcode P00609924); isolectotypes are traced at K and CAL. A preliminary morphological characterization of the species is also given, based on field surveys and examination of herbarium specimens. We noted that I. thyrsiflora is highly variable. However, we prefer to avoid, for the moment, taxonomic conclusions about the various morphotypes found, waiting the complete results of this ongoing morphological and molecular investigations.